KAJIAN STUDI LITERATUR PEOPLE MANAGEMENT: PENGARUH KEPEMIMPINAN TERHADAP KINERJATIM - Meiana Maulida Hikmawati; Amin Kiswantoro; Amri Amirrulloh; Muhammad Syaifulloh (EKOBIS, 2023)
Transformational and transactional leadership are two types of leadership that haveanappeal to be studied in research studies. This study discusses the descriptions andperspectives of each type of leadership based on literature and previous research. Transformational leadership is a more visionary type of leadership and is able tobringemployees to continue to make changes through meaningful ideas, ideas and actions. Meanwhile, transactional leadership is more structural which includes rewards andpunishments as motivation for employees. Its implementation depends on the situationandconditions as well as the culture that exists within an organization. The actions of thesetwotypes of leadership af ect team performance in an organization. Ef ective leadershipwillaf ect the success of the organization to achieve its goals. The actions of a leader arealsoable to increase the growth and development of his followers (employees), especiallypersonal growth. This motivates employees to continue to grow and develop so that theresulting performance